Proceedings of the 2nd Universitas Kuningan International Conference on System, Engineering, and Technology, UNISET 2021, 2 Dec 2022
DOI: 10.4108/eai.2-12-2021.2320216
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurial Orientation on SMEs Performance in West Java Province: Market Orientation as Mediating Variable

Abstract: In this study, we examine the effect of Entrepreneurial Orientation on the performance of SMEs by using the mediating impact of Market Orientation. We used respondents from four regions in the West Java Province of Indonesia. After the questionnaires were distributed using the purposive sampling method, a total of 188 respondents were obtained. The analytical technique used in this study was Structural Equation Modeling (SEM). From the results of the study, it was found that orientations can affect the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…A study conducted in West Java Province found that EO has a positive and significant effect on the performance of SMEs. The study also suggested that market orientation is an important variable that can bridge the relationship between EO and SME performance (Manali et al, 2022). Finally, a study explored the impact of EO and risk-sharing on organizational performance, and the influencing role of news media and public opinion.…”
Section: Discussion Of Findingsmentioning
confidence: 98%
“…A study conducted in West Java Province found that EO has a positive and significant effect on the performance of SMEs. The study also suggested that market orientation is an important variable that can bridge the relationship between EO and SME performance (Manali et al, 2022). Finally, a study explored the impact of EO and risk-sharing on organizational performance, and the influencing role of news media and public opinion.…”
Section: Discussion Of Findingsmentioning
confidence: 98%